(untitled) (Research, Society and Development, 2021)
The mucopolysaccharidosis (MPS) type VI is a rare lysosomal storage disease presenting leukocyte inclusions (Alder-Reilly anomaly) and lymphocytes with metachromatic inclusion surrounded by clear spaces, Gasser cells. Currently, an enzyme replacement therapy (ERT) with galsulfase is used to treat MPS type VI. This study evaluated 14 patients with MPS type VI performed cell counts Gasser before and after six months from the beginning of ERT. It was observed an average of 12.7% cells per patient, and after six months was found complete cell Gasser disappearance, proving to be an effective biomarker of response to ERT.